Evidence concerning parental exposure to pesticides and the occurrence of leukemia in offspring: a systematic review - Silva, Kennia Cristine de Souza; Oliveira, Geise Ellen Broto; Amarante, Marla Karine; Panis, Carolina (Frontiers in Pediatrics, 2025)
Leukemias are among the most common childhood cancers. Although its causes are still unclear, parents' environmental exposure to carcinogenic risk factors may have considerable potential. In this context, we revised the literature concerning parental exposure to pesticides, the development of leukemia in offspring, and the underlying molecular mechanisms involved. This systematic review was based on the PRISMA methodology. Only original studies were included; review articles and case reports were excluded. In total, 312 articles were screened. Of the 29 articles selected and 14 were included in this review. The main findings described in the studies above raise the hypothesis that parental pesticide exposure may be related to the development of leukemia in offspring. However, the literature reinforces the lack of well-designed studies highlighting the mechanism triggered by this exposure and its relationship with childhood cancer. The revised literature provides strong evidence supporting the relationship between parental exposure to pesticides and leukemia development in offspring. While gaps remain in understanding the precise mechanisms involved, the findings emphasize the potential risk posed by pesticide exposure and highlight the need for well-designed studies to clarify the underlying biological pathways.